2021
DOI: 10.3390/nu13030902
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Healthy Nordic Diet Intervention for the Treatment of Depression: A Randomized Controlled Pilot Trial

Abstract: Healthy diet interventions have been shown to improve depressive symptoms, but there is a need for randomized controlled trials (RCTs) that are double blind and investigate biological mechanisms. The primary objectives of this randomized controlled pilot trial were to test the palatability of the meals and the acceptability of the intervention in preparation for an 8-week RCT in the future, which will investigate whether a healthy Nordic diet improves depressive symptoms in individuals with major depressive di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A 8-day randomized controlled pilot trial conducted in Sweden involving 16 women and men aged between 18 and 65 years with major depressive disorder in a controlled setting with provided foods, demonstrated that a healthy ND compared to a control diet was related to a greater reduction in depressive symptoms ( 55 ). Studies with a stronger methodology, that consider a longer period and larger sample size, may help to confirm the findings of this study.…”
Section: Nordic Diet and Neurological Function: Current Evidencementioning
confidence: 99%
“…A 8-day randomized controlled pilot trial conducted in Sweden involving 16 women and men aged between 18 and 65 years with major depressive disorder in a controlled setting with provided foods, demonstrated that a healthy ND compared to a control diet was related to a greater reduction in depressive symptoms ( 55 ). Studies with a stronger methodology, that consider a longer period and larger sample size, may help to confirm the findings of this study.…”
Section: Nordic Diet and Neurological Function: Current Evidencementioning
confidence: 99%
“…This diet may have mood-stabilizing properties through altered excitatory/inhibitory status affecting the signaling of the neurotransmitters dopamine, GABA, and glutamate, as well as more effective ATP production with a reduction of reactive oxygen species production [ 66 , 67 ]. Another study currently undergoing recruitment is a pilot RCT with 8 weeks of a healthy Nordic diet versus a control diet for individuals with MDD [ 68 ]. The Nordic diet consists of a high intake of vegetables and is associated with reduced inflammation and improved metabolic markers, insulin sensitivity, and cognition [ 68 ].…”
Section: Dietary Interventions As An Emergent Strategy In the Treatme...mentioning
confidence: 99%
“…Another study currently undergoing recruitment is a pilot RCT with 8 weeks of a healthy Nordic diet versus a control diet for individuals with MDD [ 68 ]. The Nordic diet consists of a high intake of vegetables and is associated with reduced inflammation and improved metabolic markers, insulin sensitivity, and cognition [ 68 ]. In addition, a multi-site RCT implemented the vegan diet for 18 weeks in which significant improvements in depressive symptoms were shown [ 69 ].…”
Section: Dietary Interventions As An Emergent Strategy In the Treatme...mentioning
confidence: 99%